Atrial fibrillation in the elderly: a review. (November 2014) - Hakim, Fayaz A; Shen, Win-Kuang
ABSTRACT : Atrial fibrillation (AF) is common in the elderly population. Elderly patients with AF are often asymptomatic, may have atypical presentation or may present with heart failure or thromboembolic complications. The optimal management strategy of AF in the elderly population is challenging. We present an overview of AF in elderly patients, in particular addressing the pros and cons of various management strategies, and provide a practical approach within the guidelines.